2019
DOI: 10.1080/14756366.2019.1575372
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and biological evaluation of novel derivatives of dithiodiglycolic acid prepared via oxidative coupling of thiols

Abstract: Human thioredoxin reductase 1 (TrxR1) is a selenocysteine-containing enzyme which plays a crucial role in regulating numerous redox signalling pathways within the cell. While its functioning is important in all cells, levels of TrxR1 expression are higher in cancer cells, possibly as an adaptation to much higher levels of reactive oxygen species and the need for more extensive DNA synthesis. This makes TrxR1 an attractive target for cancer therapy development. Inspired by the structure of disulphide compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Complexes 16 and 20 inhibited the activity of isolated rat TrxR1 at micromolar concentrations: IC 50 (16) = 20.4 ± 0.1 µM and IC 50 (20) = 8.5 ± 0.3 µM. We demonstrated the efficacy of 16 and 20 as modulators of intracellular TrxR1 using rat liver extracts and varying concentrations of each complex (Figure 7 and Table S1; see Experimental for details) [47].…”
Section: Inhibition Of Trxrmentioning
confidence: 81%
“…Complexes 16 and 20 inhibited the activity of isolated rat TrxR1 at micromolar concentrations: IC 50 (16) = 20.4 ± 0.1 µM and IC 50 (20) = 8.5 ± 0.3 µM. We demonstrated the efficacy of 16 and 20 as modulators of intracellular TrxR1 using rat liver extracts and varying concentrations of each complex (Figure 7 and Table S1; see Experimental for details) [47].…”
Section: Inhibition Of Trxrmentioning
confidence: 81%
“…Moreover, previously reports suggested that TrxR1 was high expressed in many cancer cells and acted as a promising target for cancer therapy 26 . Also, important evidence showed that TrxR1 inhibitors valuable for growth inhibition against human cancer cell line SH‐SY5Y, and may be act as an attractive target for cancer therapy 27 . A recent evidence demonstrated that Licochalcone A administration suppressed cell apoptosis through reducing the expression of TrxR1 in colorectal cancer cells 28 .…”
Section: Discussionmentioning
confidence: 99%
“…26 Also, important evidence showed that TrxR1 inhibitors valuable for growth inhibition against human cancer cell line SH-SY5Y, and may be act as an attractive target for cancer therapy. 27 A recent evidence demonstrated that Licochalcone A administration suppressed cell apoptosis through reducing the expression of TrxR1 in colorectal cancer cells. 28 In agreement with this article, the present study confirmed that LicE treatment significant inhibited TrxR1 expression in NB cell lines SH-SY5Y and SK-N-BE(2) at mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Another principal mechanism of tumour survival which we have been recently tackling 11,12 as a target for anticancer agent design, is that providing tumour cell defence against oxidative stress (reactive oxygen species or ROS). In particular, tumour cells have been shown to overexpress thioredoxin reductase (TrxR, EC 1.8.1.9) which contributes to their resistant phenotype characterised by higher levels of ROS 13 .…”
Section: Introductionmentioning
confidence: 99%